The paradox of resource access: influence on location decision comprehensiveness and new venture performance - Nastaran Simarasl; Pooya Tabesh; Younggeun Lee (New England Journal of Entrepreneurship)
Purpose – This research aims to theorize how a critical factor, resource access, can paradoxically impact the comprehensiveness of venture location decision processes and the relationship between decision comprehensiveness and new venture performance. To do so, the authors focus on nascent entrepreneurs’ venture location decision processes and introduce resource access as a double-edged sword. Design/methodology/approach – In this conceptual article, the authors draw from the strategic decision-making and resource mobilization literature to theorize about the new venture location decision-making process and its performance implications. Findings – By uncovering the paradox of resource access, the authors propose that high levels of resource access create a paradoxical situation in which nascent entrepreneurs are less likely to use comprehensive decision processes when their benefits are at their greatest. Originality/value – This work contributes to entrepreneurship research on new venture location and resource mobilization in three important ways. First, the authors advance the literature on nascent entrepreneurs’ location decision-making processes by introducing “location decision comprehensiveness” as a decision process construct and juxtaposing it with resource access to uncover the entrepreneurial decision-making process. Second, the authors develop a more nuanced theorization of the location choices made by nascent entrepreneurs instead of relying on generalized conclusions drawn from well-established corporations’ location decisions. Last, the authors extend the literature on resource mobilization in entrepreneurship by shedding light on the paradoxical aspect of resource access. While previous research has emphasized the favorable effects of resource access on new venture processes and outcomes, the authors contend that it can also negatively impact entrepreneurs’ ability to make effective decisions.